Validation of the Dash, Bhondave, and Gadekar Score System to Predict the Difficulties of Laparoscopic Cholecystectomy - Tito Ade Putra; I Made Mahayasa; Tjok Gde Bagus Mahadewa (HM Publisher, 2022)
Background: One of the treatment options for cholelithiasis is laparoscopic cholelithiasis. The challenge of this procedure is to determine the level of surgery. Methods: This analytic cross-sectional study was conducted at Sanglah Hospital Denpasar from January 2019 to September 2020. Several risk factors data were assessed according to the Risk Scoring System for Laparoscopic Cholecystectomy. Receiver Operating Characteristic (ROC) curve was plotted to determine the cut-off score based on the most optimal sensitivity and specificity to predict the difficulty of surgery. Univariate statistical analysis was conducted based on the type of data with a p-value <0.05 considered significant. Results: From a total of 62 laparoscopic cholecystectomies, 36 (58.1%) case was a simple surgery, and 26 (41.9%) was difficult surgery. In the difficult surgical group, 17 surgeries (27.4%) were more than 60 minutes, nine surgeries (14.5%) with bile spillage, and one surgery (1.6%) with ductal injury. The scoring system had a sensitivity of 86.1%, a specificity of 76.9%, a positive predictive value of 83.7%, and a negative predictive value of 80%. Conclusion: A scoring system is a promising approach to estimating the difficulty of laparoscopic cholecystectomy. Further study to improve this scoring system is necessary.